ANALISIS PENERAPAN PRINSIP ETIKA BISNIS ISLAM TERHADAP TRANSAKSI JUAL BELI PADA MARKETPLACE SHOPEE - Bambang Priyowahono (Journal Khafi : Journal Of Islamic Studies, 2024)
Business ethics refers to a general concept that corrects someone to adopt it in their behavior in the business sector. It is a character that is used to discriminate between a good and bad thing, right or wrong, should or should not, etc. People can often grasp in the business sector about a company that has the primary purpose of acquiring very much profit in this day and age of quick technological advancement. It is conceivable for business actors to dominate other business actors in an economic legal system that depends on little capital and seeks maximum profit, in which case the latter will likely do everything within their power to secure very enormous profits. On the other hand, Islamic law explains how the Prophet Muhammad SAW is an example of the ethics of conducting business in accordance with sharia. The purpose of this study is to determine whether applying sharia business ethics—which are in conformity with Islamic law—to online transactions including purchases and sales on the Shopee Marketplace is appropriate. This study employed a descriptive method to precisely investigate the qualities of the thing and explain it as it is in order to present reality. The findings demonstrated that the application of business ethics practices has not been in line with Islamic business ethics principles, nor has it been applied to the practice of buying and selling in online retailers on Marketplace Shopee